Balsam Poplar Buds: Extraction of Potential Phenolic Compounds with Polyethylene Glycol Aqueous Solution, Thermal Sterilization of Extracts and Challenges to Their Application in Topical Ocular Formulations - Monika Stanciauskaite; Mindaugas Marksa; Liudas Ivanauskas; Kristina Ramanauskiene (MDPI AG, 2022)
Phenolic compounds of natural origin have been valued for their beneficial effects on health since ancient times. During our study, we performed the extraction of phenolic compounds from balsam poplar buds using different concentrations of aqueous polyethylene glycol 400 solvents (10-30% PEG400). The aqueous 30% PEG400 extract showed the best phenolic yield. The stability of the extract during autoclave sterilization was evaluated. The extract remained stable under heat sterilization. Ophthalmic formulations are formed using different concentrations (8-15%) of poloxamer 407 (P407) together with hydroxypropyl methylcellulose (0.3%), sodium carboxymethyl cellulose (0.3%) or hyaluronic acid (0.1%). Physicochemical parameters of the formulations remained significantly unchanged after sterilization. Formulations based on 12% P407 exhibited properties characteristic of in situ gels, the gelation point of the formulations was close to the temperature of the cornea. After evaluating the amount of released compounds, it was found that, as the concentration of polymers increases, the amount of released compounds decreases. Formulations based on 15% P407 released the least biologically active compounds. Sterilized formulations remained stable for 30 days.